2020
DOI: 10.1039/c9nj06005g
|View full text |Cite
|
Sign up to set email alerts
|

“Sweet” ionic liquids comprising the acesulfame anion – synthesis, physicochemical properties and antifeedant activity towards stored product insects

Abstract: The synthesized “sweet” ionic liquids comprising acesulfame anion proved to be effective antifeedants with designer physicochemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 58 publications
4
17
0
Order By: Relevance
“…It is noteworthy that the transition from hydrophilic to hydrophobic character occurred in the alkyl elongation from hexyl ( 3 ) to octyl ( 4 ). This observation is consistent with other reports on ILs; 15 , 39 however, the hydrophobic character may also be demonstrated by ILs containing shorter substituents such as butyl. 18 Moreover, the increase in measured values of K OW due to chain elongation were not as drastic as in the case of HILs comprising other herbicides, such as bromoxynil, 13 fomesafen, 14 picloram, 15 and 2,4-DP.…”
Section: Results and Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It is noteworthy that the transition from hydrophilic to hydrophobic character occurred in the alkyl elongation from hexyl ( 3 ) to octyl ( 4 ). This observation is consistent with other reports on ILs; 15 , 39 however, the hydrophobic character may also be demonstrated by ILs containing shorter substituents such as butyl. 18 Moreover, the increase in measured values of K OW due to chain elongation were not as drastic as in the case of HILs comprising other herbicides, such as bromoxynil, 13 fomesafen, 14 picloram, 15 and 2,4-DP.…”
Section: Results and Discussionsupporting
confidence: 93%
“…The differences in the solubilities in the least polar solvents support the thesis that ionic liquids are immiscible with liquids that possess low dielectric constants. 39 Hence, none of the obtained ILs dissolved in hexane (ε r = 1.9) or toluene (ε r = 2.4), whereas four were miscible with ethyl acetate (ε r = 6.0) and almost all were soluble in isopropanol (ε r = 19.9).…”
Section: Results and Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This is consistent with the nonpolar secondary metabolites of terpenoids and steroids. Most of the terpenoid compounds also contain an -OH group so that the presence of a hydroxyl group substituent attached to the hydrocarbon chain can be attracted by semi-polar and even polar solvents (Stachowiak et al 2020). So it can be concluded that L. obtusa positively contains secondary metabolites in the form of terpenoids and steroids.…”
Section: Thin Layer Chromatography Profile Analysismentioning
confidence: 99%